A Multicultural Interactive Digital Book: Promoting Tolerance and Multiculturalism to Elementary School Students - Andarini Permata Cahyaningtyas; Yulina Ismiyanti; Moh Salimi (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aimed to develop a multicultural interactive digital book for higher grade students of elementary school to promote tolerance and multiculturalism. The research used Research and Development method with ADDIE design that contained five steps: analyzing, designing, developing, implementing, and evaluating. First, the need analysis was conducted to find out what kind of literature can help students learn tolerance and multiculturalism. Next, the product was designed based on students' needs and characteristics. After that, the product was developed. There were nine experts involved in this process to validate the product based on five indicators (language, characteristics of realistic story, tolerance, multiculturalism, and characteristics of digital book). The product was declared as very feasible with score 0.91, 0.94, 0.89, 0,94, and 0.89 respectively. Then, the implementation was conducted in SDIT Asshodiqiyah, Kota Semarang. There were two teachers and 48 students who gave product evaluations. The practicality test result showed that the product is very practical based on the evaluation from teachers and students evaluation, respectively, with 83.3% and 81.3%. All of the data in this study were collected through online questionnaires due to Covid-19 pandemic. For further recommendation, this product needs to be experimented with to determine whether it has a positive and significant effect on students' understanding of tolerance and multiculturalism.